Ovarian stimulation in women over 38 years of age - Ruiz Flores, Francisco J. (2014)
Age when women start looking to have their first pregnancy is being postponed in developed societies. This delay results in reduction in maternal fecundability that starts at age 35 and is significant at age 40 and over. In this review we recount ovarian stimulation in women over 38 years.